County public safety center gets help with 911 calls. (American City & County, 2000)
The measures taken by Sumner County, Tennessee, to improve its 911 call management are described. The county installed a computer-aided dispatch system called PSAP Map. This new software tool automatically grabs all inbound 911 calls, both landline and wireless, and allows dispatchers to view the callers' locations on a computerized map.